2019
DOI: 10.1007/s00167-019-05555-7
|View full text |Cite
|
Sign up to set email alerts
|

Difference in joint line convergence angle between the supine and standing positions is the most important predictive factor of coronal correction error after medial opening wedge high tibial osteotomy

Abstract: Purpose Coronal correction errors after medial opening wedge high tibial osteotomy (MOWHTO) occasionally occur even with the assistance of navigation. The purpose of the present study was to determine the navigation accuracy in MOWHTO and to identify factors that affect the coronal correction error after navigation-assisted MOWHTO. Methods A total of 114 knees treated with navigation-assisted MOWHTO were reviewed retrospectively. Mechanical axis (MA) on standing radiograph and medial proximal tibial angle (MPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 42 publications
2
60
2
1
Order By: Relevance
“…The effect of WB on the JLCA was less frequently investigated so far. However, So et al showed a mean difference of 1.8°between WB and NWB conditions for the measurement of JLCA [32], which is comparable to the results of this study. At the same time, they found it to be the most important predicting factor for coronal correction discrepancy after medial opening-wedge high tibial osteotomy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The effect of WB on the JLCA was less frequently investigated so far. However, So et al showed a mean difference of 1.8°between WB and NWB conditions for the measurement of JLCA [32], which is comparable to the results of this study. At the same time, they found it to be the most important predicting factor for coronal correction discrepancy after medial opening-wedge high tibial osteotomy.…”
Section: Discussionsupporting
confidence: 91%
“…Besides the need for 3D preoperative planning, it is important to incorporate WB into the surgical planning workflow, not to neglect the resulting differences in measuring lower limb parameters caused by limb loading [4,28,32]. Correctly estimating the HKA is mandatory, as precise axis correction in coronal realignment surgery is crucial for a successful postoperative result, and under-or overcorrection, probably partly as a result of the measurement discrepancies, was shown to be the main reason for clinical failure [3,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, JLCA changes can be anticipated [4,19,45] as well as accounting for the changes in soft tissue correction [27,44]. An equation has been proposed to define the acceptable intra-articular correction with the aim of achieving a more anatomic osteotomy while considering JLCA.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of overcorrection due to a change in JLCA after OWHTO can explain this difference. 8,16,19,22 Whereas several studies 8,19 have proposed a method to predict overcorrection due to soft tissue effects after OWHTO, there are some limitations to accurately predicting this soft tissue effect preoperatively. Although postoperative knee JLO may increase due to an increase in limb adduction by overcorrecting the overall alignment, the local effect of the decrease in JLO caused by the decrease in JLCA compensates for the increase in JLO due to overcorrection.…”
Section: Discussionmentioning
confidence: 99%